Series connection of quantum Hall resistance array and programmable Josephson voltage standard for current generation at one microampere. (1st December 2022) - Chae, Dong-Hun; Kim, Mun-Seog; Oe, Takehiko; Kaneko, Nobu-Hisa
Abstract: An accurate current can be realized by a series connection of an invariant voltage and resistance with zero interconnection resistance in the framework of Ohm's law. In practice, however, accurate current realization is limited by the temporal drift and instability of employed resistors, solid-state voltage sources and interconnection wires against environmental fluctuations, such as temperature or atmospheric pressure. Here, we generated a current of 1 μA, determined by the Josephson voltage and quantized Hall resistance array (QHRA). A programmable Josephson voltage standard (PJVS), 1 MΩ QHRA and ultrastable low noise current amplifier (ULCA) are connected in series to generate and measure a current of 1 μA. The expected current is calculated as the ratio of the Josephson voltage to the QHRA plus the output resistance of the PJVS. The relative difference between the current measured by the ULCA and the calculated current is as small as 40 nA A −1 with a combined measurement uncertainty ( k = 1) of 0.13 μA A −1 .